A2 = 216 Дж
A3 = 144 Дж
Объяснение:
i1 = 1 A
i1=i2+i3
U=i2*R2 = (i1-i3)*R2;
U=i3*R3;
(i1-i3)*R2 = i3*R3;
(1-i3)*10 = i3*15;
i3 = 0,4 A
i2 = i1 - i3 = 1-0,4 =0,6 A
A2 = i2^2 *R2 *t = 0,6^2 *10 *60 c = 216 Дж
A3 = i3^2 *R3 *t = 0,4^2 *15 *60 c = 144 Дж
A2 = 216 Дж
A3 = 144 Дж
Объяснение:
i1 = 1 A
i1=i2+i3
U=i2*R2 = (i1-i3)*R2;
U=i3*R3;
(i1-i3)*R2 = i3*R3;
(1-i3)*10 = i3*15;
i3 = 0,4 A
i2 = i1 - i3 = 1-0,4 =0,6 A
A2 = i2^2 *R2 *t = 0,6^2 *10 *60 c = 216 Дж
A3 = i3^2 *R3 *t = 0,4^2 *15 *60 c = 144 Дж